DOI: 10.26512/2016.02.d.21097
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização agronômica e fisíco-química de progênies de maracujazeiro azedo (Passiflora edulis Sims) no Distrito Federal

Abstract: TÍTULO DA TESE DE DOUTORADO: Caracterização agronômica e fisíco-química de progênies de maracujazeiro azedo (Passiflora edulis Sims) no Distrito Federal. GRAU: MESTRE. ANO: 2016 É concedida à Universidade de Brasília permissão para reproduzir cópias desta dissertação de mestrado e para emprestar ou vender tais cópias somente para propósitos acadêmicos e científicos. O autor reserva os outros direitos de publicação e nenhuma parte desta dissertação de mestrado pode ser reproduzida sem a autorização por escrito … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
1

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
5
4
1
Order By: Relevance
“…Our results are in conformity with Nogueira (2016), who also reported that genotypes Rosa Intenso and MSCA were moderately susceptible to PWD, showing the lowest severity scores among the genotypes tested when inoculated with the same CABMV isolate, but on a distinct evaluation date. Although our study did not differentiate genotypes for PWD severity, it is important to recognize that MAR20#41(1.6) and Rosa Intenso (1.6) exhibited 11.1% less mean PWD severity than the highest value identified (1.8), demonstrating a slightly greater resistance to PWD.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in conformity with Nogueira (2016), who also reported that genotypes Rosa Intenso and MSCA were moderately susceptible to PWD, showing the lowest severity scores among the genotypes tested when inoculated with the same CABMV isolate, but on a distinct evaluation date. Although our study did not differentiate genotypes for PWD severity, it is important to recognize that MAR20#41(1.6) and Rosa Intenso (1.6) exhibited 11.1% less mean PWD severity than the highest value identified (1.8), demonstrating a slightly greater resistance to PWD.…”
Section: Resultssupporting
confidence: 93%
“…Our findings are corroborated by Costa et al (2018) who also verified that MAR20#2005 (S) and MSCA (S) presented higher severity scores as compared to other genotypes when inoculated with UnB-1393 Xap strain during the wet season. Conversely, Nogueira (2016) found greater susceptibility of Rosa Intenso (MS), MAR20#41 (S), and MSCA (S) when 90-day-old plants were inoculated with UnB-1393 Xap strain during the same study period of this report.…”
Section: Resultssupporting
confidence: 43%
“…PWD severity assessments did not identify any difference among progenies (P > 0.05) and they were classified as moderately susceptible, in accordance with the mean number obtained from the grading scale (Table 3). These findings are corroborated by Nogueira (2016), who also recorded moderate susceptibility of progenies Rosa Intenso, MAR20#41, EC-3-0, and BRS GA1 when inoculated with a distinct CABMV isolate (UnB-Fal) in the same season of this study. Although no differences were detected, progeny MAR20#41 (1.6) exhibited 30.4% less severity while progenies MAR20#2005 (1.9) and Rosa Intenso 1 (1.9) presented 17.4% less severity than AR2 (2.3) and MAR20#39 (2.3).…”
Section: Resultssupporting
confidence: 88%
“…Despite the lack of difference among progenies, it is important to emphasize that MAR20#2005 (3.5) and BRS GA1 (3.6) revealed severity scores 10.3 and 7.7%, respectively, lower than FB200 (3.9). Genotype susceptibility was also observed in other studies when a distinct Xap strain (UnB-1393) was inoculated on sour passion fruit plants using the same bacterial suspension concentration in the wet (Costa et al, 2018a) and dry (Nogueira, 2016;Costa et al, 2018b) seasons. However, lower severity scores and progeny × evaluation date interaction were recorded during the dry season both by Nogueira (2016) and Costa et al (2018b) for progenies of the same genotypes evaluated in this study.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation